An empirical study of the relationship between Islamic modes of finance and financial intermediation - Hafnida, Hafnida; Maamor, Selamah; Abdullah, Hussin (Canadian Center of Science and Education, 2015)
Islamic modes of finance become new phenomenon in financial system. Islamic modes of finance are designed to facilitate financing by the principles in Islamic Sharia, such as muḍārabah, mushāraka and sukuk.In addition financial inter mediation is an important indicator of economic development as well as economic growth.The objective of this study is to determine the relationship between Islamic modes of finance and Islamic financial inter mediation by using case study of Malaysia, Indonesia and Jordan.This study employed fixed effect and random effect through time series data from 2001-2010 for both Malaysia and Indonesia. Liquid liabilities, private sector credit and Islamic modes of finance such as muḍārabah, mushārakah, murābaḥa, ‘istiṣnā, ‘ijārah used as independent variables that expected to be influence Islamic financial intermediation as well as economic growth.Findings show that Islamic mode of finance which include murābaḥa, mushārakah, muḍārabah, ‘istiṣnā, ijārah.While, private sector credit as well as liquid liabilities are not affect Islamic financial inter mediation.